2020
DOI: 10.3389/fpsyt.2020.00735
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Cognitive Behavior Therapy Only for the Young? A Secondary Analysis of a Randomized Controlled Trial of Depression Treatment

Abstract: Background: Late-life depression is a major public health concern, driving the development of complementary treatment options. This study investigates the effectiveness and acceptability of internet-based Cognitive Behavioral Therapy (iCBT) in older individuals (60+ years) compared to younger age groups. Materials and Methods: Secondary analysis of a cluster-randomized controlled trial with 647 (18-82 years; mean 43.9) mild to moderately severe depressed primary care patients receiving either iCBT + treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Sociodemographic information included age, gender, educational and vocational qualification, marital status, and occupation. We summarized participants in three age groups (26–39 years, 40–59 years, and ≥60 years) according to Pabst et al [ 31 ] to generate data on resilience according to age. Information on educational and vocational qualifications was classified into low, middle, and high education according to the Comparative Analysis of Social Mobility in Industrial Nations (CASMIN) educational classification [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic information included age, gender, educational and vocational qualification, marital status, and occupation. We summarized participants in three age groups (26–39 years, 40–59 years, and ≥60 years) according to Pabst et al [ 31 ] to generate data on resilience according to age. Information on educational and vocational qualifications was classified into low, middle, and high education according to the Comparative Analysis of Social Mobility in Industrial Nations (CASMIN) educational classification [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The present observational cross-sectional study presents quantitative data derived from a spin-off GP survey about 2.5 years subsequent to @ktiv trial. The study design and results of the preceding @ktiv trial have been described elsewhere [14,15,23,27]. Within the trial, N = 647 GP patients were recruited via N = 112 GP practices in central Germany.…”
Section: Study Design and Samplementioning
confidence: 99%
“…Electronic mental (e-mental) health involves digital interventions leveraging the Internet and related technologies, such as smartphone apps, websites, virtual reality-based interventions, or social media, to deliver mental health services, in order to promote and to improve mental health [8][9][10][11]. Even though effect sizes have been reported to be higher in guided interventions [12], unguided interventions have also been proven to be effective and are viable treatment and self-help options [13][14][15][16][17]. According to a new individual participant data (IPD) network meta-analysis, unguided Internet-based cognitive behavioral therapy (iCBT) is just as effective in improving depressive symptoms among individuals with mild and subthreshold depression as guided iCBT [17].…”
Section: Introductionmentioning
confidence: 99%
“…An emerging body of research also suggests that iCBT is acceptable and potentially effective in reducing depressive symptoms in later life [ 9 ]. In addition, a recent randomized controlled trial reported no significant age-related differences in iCBT effectiveness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%